Atomically dispersed metal catalysts for the electrochemical nitrogen reduction reaction. Issue 42 (21st October 2022) - Gu, Hongfei; Chen, Wenxing; Li, Xinyuan
Abstract : The current breakthroughs in designing atomically dispersed metal catalysts for the electrochemical N2 reduction reaction are summarized from both experimental and theoretical points of view. The outstanding performances of these catalysts are emphasized. Abstract : The electrochemical nitrogen reduction reaction (eNRR) is considered an environmentally friendly approach to synthesize ammonia (NH3 ) under ambient conditions. However, the undesirable NH3 yield rate and Faraday efficiency make it a challenge to characterize and evaluate the performance of eNRR catalysts, which severely hinders the development of the eNRR in both the research field and industry applications. Recently, the precise detection protocols towards the produced NH3 from the eNRR, such as control measurements and quantitative isotope measurements, have made it possible to scientifically analyze the accurate catalytic performance. By virtue of the gradually developed detection strategies, atomically dispersed metal catalysts (ADMCs) with high atomic utilization efficiency and unique electronic structures, have been recognized as promising catalysts to enhance eNRR performance. Herein, the current breakthroughs in designing ADMCs for the eNRR are summarized, which are necessary for the further development of the eNRR and ADMCs. In this review, firstly, the fundamental principles of the eNRR are presented to illustrate the evaluation criterion of eNRR performance and catalytic mechanisms. Secondly, the construction of ADMCs for the eNRR from both experimental and theoretical points of view is systematically summarized. Thirdly, the current progress with outstanding ADMCs in the eNRR is emphasized. Finally, the perspectives are discussed for constructing high-performance ADMCs in the eNRR.